2011
DOI: 10.2106/jbjs.j.01646
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weekly Risedronate on Periprosthetic Bone Resorption Following Total Hip Arthroplasty

Abstract: Risedronate taken once weekly for six months following total hip arthroplasty was effective in reducing periprosthetic bone resorption around an uncemented femoral stem up to one year after surgery but had no discernible effect on implant migration or clinical outcome. Future studies of bisphosphonate treatment following total hip arthroplasty should focus on clinically relevant end points such as the risks of fracture and revision arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 195 publications
(331 reference statements)
3
54
1
2
Order By: Relevance
“…A number of previous studies have indicated that the approaches from the front of the joint have a distinct advantage of reducing the rate of postoperative dislocation [14,43,45]. Our findings confirm these observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of previous studies have indicated that the approaches from the front of the joint have a distinct advantage of reducing the rate of postoperative dislocation [14,43,45]. Our findings confirm these observations.…”
Section: Discussionsupporting
confidence: 91%
“…The main advantage of anteriorly based approaches has been reduction in the incidence of hip dislocation [14,43,45,51]. However, some studies have expressed concern regarding implant malposition that could compromise long-term survival of the implant [3,33].…”
Section: Introductionmentioning
confidence: 99%
“…At least up to 2 years after surgery, the ultra-short stem preserves femoral bone, which is advantageous should a later stem revision be necessary. Bone remodeling in the control group was in accordance with an earlier study with this stem by our research group (Sköldenberg et al 2011). In a study of the current ultra-short stem, Kim et al (2011a) found bone remodeling in accordance with our results.…”
Section: Discussionsupporting
confidence: 89%
“…Inadequate quantity or quality of the supporting bone can contribute to THA failure, including aseptic loosening and periprosthetic fracture [27,28]. Multiple studies have evaluated the effect of bisphosphonate use on bone mineral density (BMD) surrounding THA devices [1,2,5,12,15,16,29,32,37,38]. All the studies focused on the short-term effect of a single antiosteoporotic agent on the BMD surrounding the implant.…”
Section: Introductionmentioning
confidence: 99%